2005
DOI: 10.1021/jp053245c
|View full text |Cite
|
Sign up to set email alerts
|

Selective Removal of Metallic Single-Walled Carbon Nanotubes with Small Diameters by Using Nitric and Sulfuric Acids

Abstract: Coexistence of metallic and semiconducting carbon nanotubes has often been a bottleneck in many applications and much fundamental research. Single-walled carbon nanotubes (SWCNTs) were dissolved in HNO3/H2SO4 mixture to confirm differing reactivity between metallic (m) and semiconducting (s) SWCNTs. With HNO3/H2SO4 treatment, s-SWCNTs remained intact, while m-SWCNTs were completely removed for SWCNTs with small diameters less than 1.1 nm, which was confirmed by resonant Raman and optical absorption spectra. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
83
2
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 35 publications
12
83
2
1
Order By: Relevance
“…For further improvement, metallic CNTs incorporated in the channel should be eliminated so that the density of CNTs is able to be increased without degrading ON/OFF ratio. Selective etching of metallic CNTs based on chemical 36 , electrochemical 37 , plasma 38 and light irradiation 39 methods would be applicable for present devices.…”
Section: Discussionmentioning
confidence: 99%
“…For further improvement, metallic CNTs incorporated in the channel should be eliminated so that the density of CNTs is able to be increased without degrading ON/OFF ratio. Selective etching of metallic CNTs based on chemical 36 , electrochemical 37 , plasma 38 and light irradiation 39 methods would be applicable for present devices.…”
Section: Discussionmentioning
confidence: 99%
“…90 A more specific diameter dependence is reported upon light induced oxidation of SWCNTs in H 2 O 2 , where it was found that those SWCNTs are selectively destroyed where the transition energies between the vHs matches the photon energy of the light used for oxidation. 100 An additional selectivity towards the electronic properties of the SWCNTs was observed for the treatment of SWCNTs with nitronium ions 101 and by fluorine gas. 102 In contrast to these reactions, which are reported to lead to the complete disintegration of certain SWCNTs, reactions that lead to a selective functionalization of SWCNTs are observed.…”
Section: Variation Of Rbm Intensities Upon Functionalizationmentioning
confidence: 96%
“…In some cases this is traced back to a selective functionalization of metallic SWCNTs or to a change in the ratio of metallic to semiconducting SWCNTs due to selective removal (etching) of metallic SWCNTs, for example, after etching with NO C 2 -ions 101 and fluorine. 102 For solution-phase ozonolysis, where it was found that the small diameter SWCNTs are preferentially functionalized, an increase or decrease of the BWF line shape is observed, depending on the laser wavelength (Fig.…”
Section: Change Of G-band Line Shapementioning
confidence: 99%
“…The formation of these groups is usually accompanied by damages due to oxidation, such as structural defects, [31] shortening of tubes, [32][33][34] accumulation of carbonaceous debris, [35,36] disappearance of small diameter nanotubes, [37][38][39] and overall loss of material. [35,40] These structural degradations are very common with SWCNTs, and have also been observed for MWCNTs [41,42] after prolonged heating under reflux.…”
Section: Introductionmentioning
confidence: 99%